In vitro Release of Eosinophil Proteins in Allergic and Atopic Dermatitis Patients - L. K. Poulsen; C. M. Reimert; C. Bindslev-Jensen (Mediators of Inflammation)
To investigate whether eosinophils are stimulated in vivo or have acquired an increased susceptibility to stimuli from the coagulation cascade, the release of eosinophil proteins was compared for three groups of donors with different levels of serum IgE. (1) with atopic dermatitis (s-IgE > 5000 IU/ml, n = 11); (2) with inhalant allergy (200 < s-IgE < 2 000 IU/ml, n = 10); and (3) non-allergic (s- IgE < 100 IU/ml, n = 10). The levels of eosinophil cationic protein and eosinophil protein X (ECP, EPX) were determined in serum (clotting time = 2.0 h) and plasma. Serum and plasma ECP in normal donors demonstrated large intra-personal variations (C.V. 50–80%), but serum-ECP (mean 8.1 ng/ml) was clearly distinguishable from plasma ECP (mean 1.0 ng/ml) by a factor of 8 (range: 5.6–11.6). The ECP released during clotting was markedly increased in the atopic dermatitis group (serum:plasma ratio 13.5, p<0.003) compared with the other groups (6.7 and 5.6). EPX, having a higher plasma level, demonstrated a less pronounced release (serum: plasma ratios 2.0, 1.7 and 1.4), with no statistical difference between donor groups. Considering all donors together the levels of ECP and EPX in plasma and in serum were correlated to the number of eosinophils (coefficients of correlation 0.54-0.58, p<0.002).